Everybody matters the extraordinary power of caring for your people like family - Chapman, Bob. (New York Penguin, 2015)
Chapman and coauthor Raj Sisodia show how any organization can reject the traumatic consequences of rolling layoffs, dehumanizing rules, and hypercompetitive cultures. Once you stop treating people like functions or costs, disengaged workers begin to share their gifts and talents toward a shared future. Uninspired workers stop feeling that their jobs have no meaning. Frustrated workers stop taking their bad days out on their spouses and kids. And everyone stops counting the minutes until it's time to go home. This book chronicles Chapman's journey to find his true calling, going behind the scenes as his team tackles real-world challenges with caring, empathy, and inspiration. It also provides clear steps to transform your own workplace, whether you lead two people or two hundred thousand. While the Barry-Wehmiller way isn't easy, it is simple. As the authors put it: 'Everyone wants to do better. Trust them. Leaders are everywhere. Find them. People achieve good things, big and small, every day. Celebrate them. Some people wish things were different. Listen to them. Everybody matters.
Includes bibliographical references (pages 249-253) and index.
Keywords: Leadership